TAFSIR PERIODISASI GARA-GARA: ANALISIS PENGUBAHAN GARA-GARA DALAM EMPAT LAKON WAYANG KULIT - Ikun Sri Kuncoro (BBPPMPV Seni dan Budaya Yogyakarta, 2022)
“Gara-gara” is an important scene in the plot of shadow puppet plays. The diversity of playsperformed or documented in the written texts tends to result in a comparison study of the playswhich is based on the time or the period of the appearance of “gara-gara”. Time dimensionsof the appearance of “gara-gara” provide opportunities for the presence of similarities anddifferences. The current article puts forward the result of content analysis in a qualitativeresearch comparing and contrasting “gara-gara” of “Antasena Gugur” performed by KiSugino Siswocarito from Banyumas, “Gancaring Palasara”, a shadow puppet play fromSurakarta, “Bogadhenta Gugur” performed by Ki Hadi Sugito, and “Abimanyu Gugur”performed by Ki Timbul Cermomanggolo from Yogyakarta. The result of the content analysisdemonstrates that there is a tendency of creating differences through the alteration in “garagara” which hides the values of just a need to look different. Hence, the alteration of the coreof the pre-scene of the play and the composition of the “panakawan” in “gara-gara” can beinterpreted as a sign of periodization. “Gara-gara” is an important scene in the plot of shadow puppet plays. The diversity of playsperformed or documented in the written texts tends to result in a comparison study of the playswhich is based on the time or the period of the appearance of “gara-gara”. Time dimensionsof the appearance of “gara-gara” provide opportunities for the presence of similarities anddifferences. The current article puts forward the result of content analysis in a qualitativeresearch comparing and contrasting “gara-gara” of “Antasena Gugur” performed by KiSugino Siswocarito from Banyumas, “Gancaring Palasara”, a shadow puppet play fromSurakarta, “Bogadhenta Gugur” performed by Ki Hadi Sugito, and “Abimanyu Gugur”performed by Ki Timbul Cermomanggolo from Yogyakarta. The result of the content analysisdemonstrates that there is a tendency of creating differences through the alteration in “garagara” which hides the values of just a need to look different. Hence, the alteration of the coreof the pre-scene of the play and the composition of the “panakawan” in “gara-gara” can beinterpreted as a sign of periodization.